An Examination of the Shadow of Sexual Assault Hypothesis Among Men and Women in South Korea - Choi, Jaeyong (International criminal justice review, 2020)
Using a South Korean sample from 2010 National Crime Victim Survey, the current research examined the gender differences of fear of four different types of crime testing the shadow of sexual assault thesis, which asserts that sexual assault operates as a master offense for females. The current study provides insight into the robustness of the shadow hypothesis by controlling for various covariates (e.g., perceptions of the neighborhood and crime-related media consumption) that have been often omitted in this line of literature. Results show that the largest difference in fear between males and females was the fear of sexual assault, and based on coefficient comparison tests, fear of sexual assault was a stronger predictor of fear of other crimes among males than among females. The current study calls for future research to disentangle the shadow of sexual hypothesis in different settings and to conduct more studies specifically on men’s fear of crime.